Closed reduction and percutaneous k-wire fixation for distal end radius fractures - Ali, Tanveer; Baketh, Mohmmad Sikander; Mir, Maneer Ahmad (International Journal of Research in Medical Sciences, 2020)
Background: To evaluate radiological and functional outcome in fractures of the distal radius treated by K-wire fixation. Methods: Forty patients (16 males, 24 females) with different types of fractures of distal radius were treated. K-wire fixation was performed under axillary bolock or general anaesthesia. Anatomical restoration was evaluated by postero-anterior and lateral radiographs obtained preoperatively and at 09 months of follow up to evaluate Radial Height (RH), Radial Inclination (RI) and Volar Tilt (VT). Functional outcome was evaluated using Mayo scoring system. Results: According to Mayo score 72.5% (n=29) of our patients had excellent to good outcome while as 17.5% (n=7) had fair outcome and 10% (n=4) patients had poor outcome. Conclusions: Kirschner wire fixation is an inexpensive procedure that provides anatomic reduction, fracture fixation, and maintenance of reduction with an adequate method of immobilization.